Surplus: the politics of production and the strategies of everyday life - Morehart, Christopher T., editor; De Lucia, Kristin, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2015)
Placing the concept of surplus at the forefront of archaeological discussions on production, consumption, power, strategy, and change, this volume reaches beyond conventional ways of thinking about top-down or bottom-up models and offers a comparative framework to examine surplus, generating new questions and methodologies to elucidate the social and political economies of the past.--Provided by publisher.
Surplus: the politics of production and the strategies of everyday and life: an introduction / Christopher T. Morehart and Kristin De Lucia -- The cost of conquest: assessing the impact of Inka tribute demands on the Wanka of Highland Peru / Cathy L. Costin -- Surplus and social change: the production of household and field in pre-Aztec Central Mexico / Kristin De Lucia and Christopher T. Morehart -- Surplus in the Indus civilization: agricultural choices, social relations, political effects / Heather M.-L. Miller -- Surplus from below: self-organization of production in early Sweden / T.L. Thurston -- From surplus land to surplus production in the Viking age settlement of Iceland / Douglas J. Bolender -- Surplus capture in contrasting modes of religiosity: perspectives from sixteenth century Mesoamerica / E. Christian Wells -- Surplus houses: palace politics in the bight of Benin West Africa, 1650-1727 A.D. / Neil L. Norman -- Surplus labor, ceremonial feasting and social inequality at Cahokia: a study in social process / James A. Brown and John E. Kelly -- The sociality of surplus among late Archaic hunter-gatherers of coastal Georgia / Victor D. Thompson and Christopher R. Moore -- The transactional dynamics of surplus in landscapes of enslavement: scalar perspectives from interstitial West Africa / Ann B. Stahl -- Conclusions: Surplus and the political economy in prehistory / Timothy Earle.
Keywords: Social archaeology; Ethnoarchaeology; Surplus (Economics) -- Social aspects -- History; Surplus (Economics) -- Political aspects -- History; Production (Economic theory) -- History; Economics -- History -- To 1800; Agriculture -- History; Social change -- History; Household archaeology; Community archaeology